Divorce protection takaful / Siti Thaqifah Ruzaidy ... [et al.] - Ruzaidy, Siti Thaqifah; Embong, Siti Adibah; Mohammad Hatta, Mohammad Firdaus; Abd. Rashid, Arlinah (2021)
Divorce can be a highly unpleasant experience to anyone involved. Compared to married couples, those who are divorced may encounter several psychological and emotional effects such as greater stress, decreased life satisfaction, depression, higher medical visits, and an overall increase in mortality risk. There's also the divorce process to consider, in addition to losing the benefits of a happy marriage, which may function as a buffer against life's typical stresses. On top of all that, after divorce, divorced women especially, often face financial hardships. How can parties have involved in a divorce cope with life after divorce especially from the financial aspect? One of the ways is to have divorce protection takaful policy to cushion life after divorce. The likelihood of a bad outcome appears to fluctuate depending on how well people adjust after divorce. There are various ways that the potential of getting takaful coverage might impact a marriage. This approach addresses how the likelihood of acquiring coverage might have a direct impact on life after divorce. This research is designed to study public interest in takaful for divorce protection at a competitive rate through the primary data collection using survey questionnaires. The survey is conducted via Google Form. The sample was drawn from the general population using random selection. The data indicate that, out of all the respondents, 74% choose to acquire takaful protection to protect themselves and their children in the case of divorce. 70% respondents are willing to pay a contribution or premium of less than RM500 for divorce protection takaful, since the survey indicates that 70% respondents have a household income of less than RM3,000. The takaful that is less than RM 500 is the most suited package for Malaysians for B40 income classification in Malaysia.